Comparative assessment of mosquito biocontrol efficiency between anabantoidei native fish: climbing perch (Anabas testudineus) and three-spot gourami (Trichogastertrichopterus) - Lim, Chia Hui (2015)
Over one million people die from mosquito-borne diseases every year urging the need to control mosquito population effectively. A study was carried out for comparison of mosquito biocontrol efficiency between two species of native Anabantoids, which were climbing perch (Anabas testudineus) and three-spot gourami (Trichogastertrichopterus). For each species, three fish were used to observe their feeding on mosquito larvae for three continuous days to determine the maximum daily intake of mosquito larvae. The mosquito larvae varying in length from 5 to 6mm were placed in each tank containing either A. testudineus or T. trichopterus. The mean maximum daily intake of mosquito larvae for a 3-day period was shown to be higher in A. testudineus as compared to the T. trichopterus. Amount of mosquito larvae fed was determined by enumerating the total number of larvae ate by the fish for each day. There was significant difference (p<0.05) in mean maximum daily intake of mosquito larvae between A. testudineus(71.1±4.37) and T. trichopterus(39.2±1.57). A. testudineus which was determined with higher predatory capacity was then further tested on the mean maximum daily intake of mosquito larvae when conditioned in tanks filled with three water sources: lake water, drain water and non-chlorinated water. It was found that the maximum daily intake of A. testudineus on mosquito larvae remained consistent regardless of the different water sources introduced. There was no significant difference (p>0.05) in the mean maximum daily intake of A. testudineus conditioned in three different water sources.